Relações teóricas da organização do conhecimento com as abordagens de catalogação de assunto, indexação e análise documental: Uma análise de domínio da revista Scire (1995-2010) - Guimarães, José Augusto Chaves [UNESP] (2012)
Considering knowledge organization and representation as a theoretical line used by Information Science to face the subject approach to information, in a dialogical relation with subject cataloguing, indexing and analyse documentaire, this article carries out a domain-analysis of Scire journal (1995-2010) in order to identify the scientific production in the mentionned theoretical lines as well as their relationships. Scire constitutes an environment where members of the different paradigms have found an space to relate each other.